Eyelid-parotid metastasis: do we screen for coexisting masses? A case series. Issue 11 (24th September 2015) - Mukherjee, C; Sadiq, A; Mehta, P; Ahluwalia, H
Abstract: Objective: To report three cases illustrating that it is not unusual for a primary eyelid tumour to metastasise to the parotid gland and vice versa. Case reports: Two patients with malignant parotid tumours underwent radical parotidectomy and presented subsequently with eyelid lesions. Biopsy showed that both eyelid lesions were histologically similar to the primary parotid tumour. A third patient was noted to have ipsilateral upper eyelid and parotid gland tumours. Histology and immunocytochemistry were used to differentiate the primary tumour and the metastasis. Conclusion: These cases illustrate that tumours involving eyelids and parotid glands can present simultaneously or sequentially, and either of these structures could be the focus of primary or metastatic tumour. The important message for oculoplastic and parotid surgeons is to routinely assess both the periocular and parotid area when patients present with a mass in either structure.